Effects of taurine on the growth performance, diarrhea, oxidative stress and intestinal barrier function of weanling piglets - Zhou, Miao; Wu, Zichen; Deng, Donghua; Wang, Bin; Zhou, Xiaoling; Zhou, Bingyu; Wang, Chunping; Zeng, Yan (Frontiers in Veterinary Science, 2024)
Oxidative damage resulting from weaning stress significantly impacts the growth performance and health status of piglets. Taurine, a dietary antioxidant with diverse functions, was investigated in this study for its protective role against weaning stress-induced oxidative damage and its underlying mechanism. Forty 28-day-old male castrated weaned piglets were randomly assigned to four groups. The control group received the basal diet, while the experimental groups were fed the basal diet supplemented with 0.1%, 0.2%, or 0.3% taurine over a 28-day period. In vitro, H2O2 was utilized to induce oxidative damage to the jejunal mucosa of piglets via IPEC-J2 cells. The results demonstrated that taurine supplementation reduced the incidence of diarrhea in piglets compared to that in the control group (P < 0.05); the addition of 0.2% and 0.3% taurine led to increased average daily gain and improved feed conversion efficiency in weaned piglets, showing a linear dose-response correlation (P < 0.05).Taurine supplementation at 0.2% and 0.3% enhanced the activities of serum CAT and GSH-Px while decreasing the levels of serum NO, XOD, GSSG, and MDA (P < 0.05). Moreover, it significantly elevated the levels of GSS, Trx, POD, complex I, mt-nd5, and mt-nd6, enhancing superoxide anion scavenging capacity and the hydroxyl-free scavenging rate in the livers of weaned piglets while reducing NO levels in the liver (P < 0.05). Additionally, 0.2% and 0.3% taurine supplementation decreased serum IL-6 levels and elevated the concentrations of IgA, IgG, and IL-10 in weaned piglets (P < 0.05). The levels of occludin, claudin, and ZO-1 in the jejunum mucosa of weaned piglets increased with 0.2% and 0.3% taurine supplementation (P < 0.05). In IPEC-J2 cells, pretreatment with 25 mM taurine for 24 hours enhanced the activities of SOD and CAT; reduced the MDA content; upregulated the mRNA expression of various genes, including ZO-1, occludin, claudin-1, Nrf2, and HO-1; and reversed the oxidative damage induced by H2O2 exposure (P < 0.05). Overall, the findings suggest that the inclusion of 2% and 3% taurine in the diet can enhance growth performance, reduce diarrhea rates, ameliorate oxidative stress and inflammation, and promote intestinal barrier function in weaned piglets.